Teachers and Social Learning as a Factor of Modern Educational Competences - J. Raicevic; S. Nikolic; L. Vlasta; M. Saracevic (University of Sofia, 2017)
Modern educational process is becoming increasingly complex, subject of the influence of many intrapersonal and interpersonal factors. Conceptual basis of this work is Bandura social learning theory, which stresses the importance of the so-called, social learning, or learning by model, positioned in the educational context. The aim is to present the results of modern studies that dealt with the personality of a teacher from a model of student behavior and social learning, which mediates in the process of modeling the student behavior, as well as the performance factors of the modern educational process. The general conclusion is that the teachers' personality through a process of social learning has important influence on students' behavior and efficiency of the educational process and that the various development and educational programs aimed at the teachers' empowerment and encouraging the operation of positive social impact, can significantly contribute to the quality and improvement of the effects of the educational efforts on the school and preschool age.